2014
DOI: 10.4236/msce.2014.21001
|View full text |Cite
|
Sign up to set email alerts
|

Soot and Nanomaterials Synthesis in the Flame

Abstract: The general scheme of conversion of hydrocarbon fuels with new experimental data on the formation of fullerenes and graphenes taking into account the pressure effect is proposed for the fuel-rich flames. It is shown that the formation of fullerenes is important to the corresponding spatial orientation of PAH, possible at low pressures. The formation of hydrophobic soot surface on silicon and nickel substrates during combustion of propane-oxygen flame was studied. It is established that the hydrophobic properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Investigations on synthesis of graphene layers in hydrocarbon flame at low pressure have shown that the formation of graphene layers is occurred in sooting zone as well as at atmospheric pressure, as was shown in [22][23][24]. Figure 3 shows the Raman spectra (a) that characterizing the carbon structures are formed on nickel plate in areas 0, 1, 2, 3 (b).…”
Section: Formation Of a Layered Graphene Films In Flamesmentioning
confidence: 86%
“…Investigations on synthesis of graphene layers in hydrocarbon flame at low pressure have shown that the formation of graphene layers is occurred in sooting zone as well as at atmospheric pressure, as was shown in [22][23][24]. Figure 3 shows the Raman spectra (a) that characterizing the carbon structures are formed on nickel plate in areas 0, 1, 2, 3 (b).…”
Section: Formation Of a Layered Graphene Films In Flamesmentioning
confidence: 86%
“…The nanobeads are morphologically similar to the carbon nanopearls synthesized by Levesque and coworkers [43] by acetylene dissociation at 700 ºC on nickel catalyst nanoclusters. Puri et al [44] have determined new ways of synthesis of carbon nanotubes in the fuel-rich diffusion flames, exposed to an electric field during 2-10 min, on superhydrophobic surfaces representing nanodimensional round amorphous carbon particles deposited on a silicon substrate [45].…”
Section: Formation Of the Hydrophobic Soot In Hydrocarbon Flamesmentioning
confidence: 99%
“…The formation of hydrophobic soot surface on silicon and nickel substrates during combustion of propane-oxygen flame was studied [45]. It is stated that the hydrophobic properties are due to the presence of soot particles in the form of nanobeads.…”
Section: Formation Of the Hydrophobic Soot In Hydrocarbon Flamesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermostable and chemically inert compounds, such as silicon and aluminium oxide, are used as support for the catalyst [6,7]. Carbon nanotubes can be synthesized in a flame using iron and nickel catalysts as shown in [8].…”
Section: Introductionmentioning
confidence: 99%